Private Providers of Climate Change Services : The Role and Scope for the Private Sector in the Provision of Non-Financial Climate Change-Related Services Relevant to Water Infrastructure - Winpenny, J.T. (World Bank, Washington, DC, 2017)
Man-made climate change is affecting water infrastructure in all regions of the world, affecting large numbers of people in their daily life and the development of their societies. As part of the World Bank Water Anchor's analytical and advisory work on water and climate change, consultants have investigated how private sector services to infrastructure may address the challenges related to climate change while, at the same time, improving development opportunities for people. This report, which is one of the outcomes of the work, addresses the role of private providers of non-financial climate change-related services with relevance for water infrastructure. This report investigates to need for additional services with regard to climate change and analyzes the potential for the private sector in providing these services. The analysis focuses on the water sectors likely to be affected by climate change, that is, water resources management, irrigation and drainage, hydropower, coastal protection, flood protection, urban water supply, and sanitation as well as water quality. In addition, opportunities for mutual engagement of public and private agencies are analyzed and the perspectives of market development are explored. The central aim of the report is to deepen our understanding of the opportunities for engaging private providers of climate change services in climate change adaptation combined with socioeconomic development opportunities.